2016
DOI: 10.1038/ejhg.2016.133
|View full text |Cite
|
Sign up to set email alerts
|

Dominant variants in the splicing factor PUF60 cause a recognizable syndrome with intellectual disability, heart defects and short stature

Abstract: International audienceVerheij syndrome, also called 8q24.3 microdeletion syndrome, is a rare condition characterized by ante- and postnatal growth retardation, microcephaly, vertebral anomalies, joint laxity/dislocation, developmental delay (DD), cardiac and renal defects and dysmorphic features. Recently, PUF60 (Poly-U Binding Splicing Factor 60 kDa), which encodes a component of the spliceosome, has been discussed as the best candidate gene for the Verheij syndrome phenotype, regarding the cardiac and short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 18 publications
(26 reference statements)
4
54
0
Order By: Relevance
“…Knockout of the PUF60 ortholog in C. elegans is embryonic lethal, while studies in Drosophila implicates a critical role for the PUF60 ortholog in alternative splicing affecting developmental regulation (MacMorris, Brocker, & Blumenthal, ; Park, Parisky, Celotto, Reenan, & Graveley, ). To date, there have been 16 reported cases with SNVs in PUF60 (Figure ), of which the most common phenotypes include Intellectual disability/developmental delay, short stature, cardiac defects and a recognizable facial phenotype consisting of square face, full cheeks, prominent forehead, low set eyebrows, wide nasal bridge, broad nasal tip, long philtrum, and a thin upper lip (Table ) (Dauber et al, ; Deciphering Developmental Disorders, ; El Chehadeh et al, ; Santos‐Simarro et al, ). Moreover, brain and skeletal anomalies also seems to be common among reported cases.…”
Section: Discussionmentioning
confidence: 99%
“…Knockout of the PUF60 ortholog in C. elegans is embryonic lethal, while studies in Drosophila implicates a critical role for the PUF60 ortholog in alternative splicing affecting developmental regulation (MacMorris, Brocker, & Blumenthal, ; Park, Parisky, Celotto, Reenan, & Graveley, ). To date, there have been 16 reported cases with SNVs in PUF60 (Figure ), of which the most common phenotypes include Intellectual disability/developmental delay, short stature, cardiac defects and a recognizable facial phenotype consisting of square face, full cheeks, prominent forehead, low set eyebrows, wide nasal bridge, broad nasal tip, long philtrum, and a thin upper lip (Table ) (Dauber et al, ; Deciphering Developmental Disorders, ; El Chehadeh et al, ; Santos‐Simarro et al, ). Moreover, brain and skeletal anomalies also seems to be common among reported cases.…”
Section: Discussionmentioning
confidence: 99%
“…35 Mutations in PUF60 are found in Verheij syndrome, a condition characterized by coloboma, ventricular septal defects, digit and hip abnormalities, developmental delay, and facial dysmorphisms. 12,13 EFTUD2 mutations occur in mandibulofacial dysostosis, Guion-Almeida type (MFDGA), which presents microcephaly, developmental delay, and craniofacial malformations. 14 SF3B4 mutations are associated with Nager syndrome (NS), in which patients exhibit midface retrusion, micrognathia, absent thumbs, and radial hypoplasia.…”
Section: Craniofacial Disordersmentioning
confidence: 99%
“…Dauber et al 80 identified the first patient with a de novo heterozygous variant, p.H169Y in PUF60 . El Chehadeh et al 81 reported another five patients with de novo heterozygous variants in PUF60. All six patients identified to date manifest the same facial gestalt as seen in individuals with 8q24.3 microdeletion syndrome, also known as Verheij syndrome (MIM 615583).…”
Section: Introductionmentioning
confidence: 99%